Detection of Trypanosomiasis in Cattle by Different Blood Smear and Staining Methods - Waad Khalid Khalaf; Wasan Amjad Alobaidii (The Indian Veterinary Journal, 2024)
In most nations, including Iraq, the disease known as bovine trypanosomosis, which is spread by tsetse flies and other vectors, seriously impairs the health and production of cattle. Our study’s goals were to find out how common bovine trypanosomosis is in the Nineveh Governorate and what risk variables are linked to it. Blood samples from 120 cattle, representing a range of ages, sexes, and breed, were obtained. The blood was stained with Giemsa and Leishman stains and analyzed using standard diagnostic techniques (wet blood smear, thin and thick blood smears). The total infection rate was 18.33%(22/120). Thin blood smear method revealed the greatest infection rate (18.33%). There were significant differences (P<0.05) between males, the highest rate (26.15%), and females, the lowest rate (9.09%). Since imported cattle had the greatest infection incidence (28.07%), the study also showed that there were notable disparities in infection rates between native and imported cattle.